Relevance matters. Eighteen-month-olds' use of relevant informative pointing as a predictor of two-year-olds' language abilities / La relevancia es importante. El uso de gestos deícticos relevantes e informativos por parte de niños de año y medio como factor predictor de las capacidades lingüísticas a los dos años. Issue 4 (2nd October 2018) - Białek, Arkadiusz; Białecka-Pikul, Marta; Filip, Anna; Broda, Maria
Abstract: The significance of pointing gestures in the development of linguistic communication is linked to their referential character and formation of common ground in use of gestures and speech. Our longitudinal study aimed to define the nature of this relationship more precisely and to explore whether the relevance vs lack of relevance of a child's pointing gestures is related to development of language abilities. We developed a special protocol to measure relevant and irrelevant pointing gestures in 18-month-olds, sampled production of spontaneous speech and measured their language comprehension at two years of age. A group of 343 children was tested, and using structural equation modelling we showed that relevant gestures predict the level of development of language production and comprehension. As predicted, this association was not applied to irrelevant gestures. It is likely that a child's more frequent use of relevant pointing gestures helps the caregiver to recognize the child's communicative intentions and to comment on his/her behaviour appropriately. The identified developmental/predictive relationship is valid in both mentalistic and teleological interpretation of early communicative development.